Inclusive and sustainable business online platform for Ghana, Peru, and the United Republic of Tanzania - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The knowledge base created using data from more than 50 businesses in oil palm, cocoa, tea, coffee, sugarcane, avocado, and timber sectors, and surveys of 1,450 inclusive business participants of 12 agribusiness models in Peru, Ghana and Tanzania, was used to design a business online platform. The innovative platform has been designed, but not yet made active online, which is planned for 2022.